Transformasi Public Hearing Di Indonesia : Peningkatan Partisipasi Publik Melalui E-Legislasi Berbasis Kontrak Sosial Guna Mewujudkan Responsibilitas Kelembagaan Di Era 5.0 - Aulia, Natasya Putri; M. Ridwan Efendi; Jovanka Dwi Tusiany (Jurnal Restorasi Hukum, 2025)
Transparency and public participation in the formation of regulations in Indonesia are needed to improve the quality and legitimacy of policies. Although the principle of openness has been regulated in Law No. 13 of 2022, its application is still not optimal. The phenomenon of social movements, such as in the polemics over the revision of the Pilkada Law, shows the public's desire to be involved in the legislative process. This research proposes a social contract-based E-Legislation model through a normative juridical method, with a regulatory approach and comparative studies. This model integrates technology with E- Rulemaking and E-Petition features to enable public involvement from the planning stage to the passing of laws. Comparative studies with the UK and Australia are used to adapt the concept of Citizen Charter. The results of this research are expected to provide recommendations to increase public trust and support the achievement of the Sustainable Development Goals in the aspects of justice and strong institutions. Transparansi dan partisipasi publik dalam pembentukan peraturan di Indonesia diperlukan untuk meningkatkan kualitas serta legitimasi kebijakan. Walaupun asas keterbukaan sudah diatur dalam UU No. 13 Tahun 2022, penerapannya masih belum optimal. Fenomena social movement, seperti dalam polemik revisi UU Pilkada, menunjukkan keinginan masyarakat untuk terlibat dalam proses legislasi. Penelitian ini mengusulkan model E-Legislasi berbasis kontrak sosial melalui metode yuridis normatif, dengan pendekatan peraturan dan studi perbandingan. Model ini mengintegrasikan teknologi dengan fitur E-Rulemaking dan E-Petition untuk memungkinkan keterlibatan publik sejak tahap perencanaan hingga pengesahan undang-undang. Studi perbandingan dengan Inggris dan Australia digunakan untuk mengadaptasi konsep Citizen Charter. Hasil penelitian ini diharapkan memberikan rekomendasi untuk meningkatkan kepercayaan publik dan mendukung.